Monitoring and Evaluation Practices and Performance of the Energy Projects in Rwanda: A Case of Electricity Access Rollout Programme (EARP) - Uwibambe, Léoncie; Njenga, Gitahi (International Journal of Entrepreneurship and Project Management, 2025)
Purpose: This research aims to appraise contribution of M&E practices to energy projects performance, especially in the Electricity Access Rollout Programme Rwanda (EARP).It examined especially the contribution of planning for M&E, project baseline Surveys implementation, and Monitoring and Evaluation information system usage to EARP performance. The research involved the Program theory, Result-based theory, and the theory of change. Methodology: For the research design, a descriptive survey helped, and the target population was 15 project staff of the completed EARP in the project management unit. During this study, the researcher used a census, the entire population was considered as a sample since its number was limited. Qualitative and quantitative approaches were applied to gather data, and through interview guide and questionnaire, the researcher gathered primary data while secondary data were gathered from various official reports. After collecting data, the researcher used SPSS V.23 for their process and analysis. The content analysis techniques served to analyze data from interviews, and reports. The frequencies, percentages, standard deviation, and means known as descriptive statistics helped the researcher in defining the data, Pearson correlational and regression statistics were used to set up relationships concerning the variables and the significance levels. The research results were finally represented using graphs and tables. Findings: According to the research findings, the majority of participants agreed that M&E planning contributed to the performance of EARP (mean=4.31, Std =0.78). Furthermore, they indicated that M&E planning and EARP performance were positively correlated with a Pearson correlation coefficient of r=0.632, and p-value= 0.01 <0.05 significance level. Also, a great number of participants agreed that baseline implementation contributed to EARP performance (mean=4.37, Std =0.813), and a strong positive correlation was established between baseline implementation and EARP performance, the Pearson correlation coefficient was r=0.832 and the p-value=0.00<0.05 the significance level. Lastly the mean and the standard deviation for the M&E Information System were (mean= 4.08, and Std= 1.04) respectively, most participants agree that M&E IS contributed to EARP performance. Nevertheless, the standard deviation was greater than one implying a large spread of responses from the mean, thus no consensus among respondents. The Pearson coefficient was r=0.170 with a p-value =0.544>005 and this value implied that no significant correlation existed between the M&E Information System usage and EARP performance as it was greater than the significance level. A regression model of the predictors against the performance of EARP yielded R-square value of 0.731, hence the three components under study could explain 73.1% of variation in EARP project performance with F=9.128, p-value=0.003<0.05. M&E Planning (β=0.228, P value= 0.04), Baseline Survey Implementation (β=0.437, P value= 0.020), M&E Information System Usage (β=-0.54, P value= 0.74) respectively. Unique Contribution to Theory, Practice and Policy: The researcher recommends those involved in project management especially energy projects or programs to adopt a robust, comprehensive, and user-friendliness M&E information system and promote M&E practices. This research may benefit different project management teams as it may provide them with the fundamental information to effectively track and measure projects. Furthermore, it may benefit several energy sector stakeholders to optimize the process of project development and promote performance for energy projects.